The power of shareholder votes: Evidence from uncontested director elections - Aggarwal, Reena; Dahiya, Sandeep; Prabhala, Nagpurnanand R. (Journal of Financial Economics, 2019)
This paper asks whether dissent votes in uncontested director elections have consequences for directors. We show that contrary to popular belief based on prior studies, shareholder votes have power and result in negative consequences for directors. Directors facing dissent are more likely to depart boards, especially if they are not lead directors or chairs of important committees. Directors facing dissent who do not leave are moved to less prominent positions on boards. Finally, we find evidence that directors facing dissent face reduced opportunities in the market for directors. We also find that the effects of dissent votes go beyond those of proxy advisor recommendations.